2004
DOI: 10.1111/j.1471-0528.2004.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher order repeat caesarean sections: how safe are five or more?

Abstract: Objective To determine the maternal morbidity and mortality associated with multiple repeat caesarean sections. Design Retrospective study.Setting Security Forces Hospital serving Ministry of Interior and Security Forces personnel in Riyadh, Kingdom of Saudi Arabia. Population Three hundred and eight case records undergoing between fifth and ninth caesarean section (mean 7) were studied and compared with a control group of 306 patients undergoing third or fourth caesarean section during the period January 1994… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
57
6
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 11 publications
11
57
6
4
Order By: Relevance
“…This is similar to birth weights by Sobande A and Rashid M et al where mean birth weight were 2.972 kg and 2.966 kg respectively. 2,6 Birth weights were lower compared to study by Macones GA and Cahill AG et al in which mean birth weight was 3.392kg and 3.046kg respectively. 7,8 Lower birth weight can be explained by the fact that the patients in our country are constitutionally small as compared to their western counterparts along with anaemia, preeclampsia, abnormal placentation and multitude of social problems.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…This is similar to birth weights by Sobande A and Rashid M et al where mean birth weight were 2.972 kg and 2.966 kg respectively. 2,6 Birth weights were lower compared to study by Macones GA and Cahill AG et al in which mean birth weight was 3.392kg and 3.046kg respectively. 7,8 Lower birth weight can be explained by the fact that the patients in our country are constitutionally small as compared to their western counterparts along with anaemia, preeclampsia, abnormal placentation and multitude of social problems.…”
Section: Discussioncontrasting
confidence: 54%
“…As per Rashid M et al 25%, Nisenbalt V et al 11% and Robert M. Silver et al 22% required obstetrics hysterectomy. [2][3][4] Our study showed higher rates compared to all the above studies, although the rates are falling due to advent of conservative techniques in management of adherent placenta. As per study by AF Hundley, 90% of women were successfully managed with conservative treatment using methotrexate therapy.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Our study found a significant increase in the rates of placenta praevia (16%), placenta accreta (14%), MOH (18%), blood transfusion (17%), hysterectomy (9%), visceral damage (5%) and critical care admission (13%) in women undergoing MRCS compared with women having caesarean sections after fewer previous procedures. Other studies of women undergoing their fifth or greater caesarean section describe lower rates of placenta praevia (between 2% and 4%), 9,12,14 placenta accreta (between 1% and 3.5%) 9,12 and hysterectomy (between 0.8% and 5%). 9,12,14 These differences may be accounted for by our study being the only prospective population, rather than a hospital-based cohort, and therefore encompassing deliveries of all complexities occurring in local and tertiary units.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies of women undergoing their fifth or greater caesarean section describe lower rates of placenta praevia (between 2% and 4%), 9,12,14 placenta accreta (between 1% and 3.5%) 9,12 and hysterectomy (between 0.8% and 5%). 9,12,14 These differences may be accounted for by our study being the only prospective population, rather than a hospital-based cohort, and therefore encompassing deliveries of all complexities occurring in local and tertiary units. However, a limitation of this study is the relatively small cohort size, which may also account for discrepancies in comparisons with other studies.…”
Section: Discussionmentioning
confidence: 96%